2005
DOI: 10.2307/3647710
|View full text |Cite
|
Sign up to set email alerts
|

Going It Alone? Strategic Entry under Mixed Electoral Rules

Abstract: Recent studies on strategic voting and entry in elections that combine plurality or majority and proportional representation (PR) have found candidate placement in single-member district (SMD) races to improve a party's PR performance. The primary implication of the existence of "contamination effects" is that parties have an incentive to nominate candidates in as many single-member districts as possible. Pre-electoral coordination in the majoritarian component of mixed electoral systems, however, is far from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 14 publications
1
43
0
4
Order By: Relevance
“…The existing literature on mixed electoral systems has examined such issues as intracoalition conflicts between parties (Ferrara and Herron 2005;Mudambi and Navarra 2004;Shugart and Wattenberg 2001) and reform incentives of the ruling party (Bawn 1993;Boix 1999;Remington and Smith 1996), but the welfare property and the optimality of mixed systems have not received much attention. This seems partly due to the difficulty of modeling multiple elections under varying degrees of mixture between the two pure systems.…”
Section: Introductionmentioning
confidence: 98%
“…The existing literature on mixed electoral systems has examined such issues as intracoalition conflicts between parties (Ferrara and Herron 2005;Mudambi and Navarra 2004;Shugart and Wattenberg 2001) and reform incentives of the ruling party (Bawn 1993;Boix 1999;Remington and Smith 1996), but the welfare property and the optimality of mixed systems have not received much attention. This seems partly due to the difficulty of modeling multiple elections under varying degrees of mixture between the two pure systems.…”
Section: Introductionmentioning
confidence: 98%
“…Some have expressed concerns that voters can be confused by the existence of two sets of rules which translate their votes into seats, and such confusion can discourage participation, produce results that are not consistent with voters' preferences, and undermine system legitimacy (Cox and Schoppa, 1998). Others have suggested that mixed systems suffer from "contamination" effects that alter the incentives of parties and voters (Ferrara and Herron 2005). In this view, the combination of two sets of electoral rules are not truely independent from one another.…”
Section: Introductionmentioning
confidence: 99%
“…Cox and Schoppa (2002) find that German parties consistently run SMD candidates everywhere even when their candidates have little chance of winning. The decision to "go it alone" rather than withdraw is intended to boost their share of the party list vote by either putting a human face on the party and/or possibly benefiting from voter confusion (Ferrara and Herron 2005). If this strategy is effective, then it raises a potential problem for MMP systems, where the party list vote is used to determine the partisan balance in the legislature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies show that parties form electoral coalitions to increase their legislative seat share (Blais and Indridason 2007;Ferrara and Herron 2005;Golder 2005;Kaminski 2001). Coalitions are vote or seat superadditive (subadditive) if they provide their members with a higher (lower) share of the vote or seats than the total share that these parties would obtain when running separately (Kaminski 2001).…”
Section: Electoral Benefitsmentioning
confidence: 99%